A general theory to explain heart rate and cardiac contractility changes with advancing age - Tsutsui, Kenta (2016)
Sinus node dysfunction and chronic heart failure have been, and will continue to be , major health issue issues in humans for the foreseeable future future. The heartbeat originateoriginates from spontaneously firing sinoatrial nodal (SAN) pacemaker cells. A coupledcoupled-clock system underlies the robust and flexible automaticity in these cells cells. The basal action potential (AP) firing rate of SAN cells is largely determined by the degree of phosphorylation o of critical proteins in th the coupledcoupled-clock system. Autonomic neuronal signaling from the brain effects changes in AP firing rate via modulatmodulation of cAMP and cAMP cAMP-mediated PKAPKA-dependent phosphorylationphosphorylation. Age -associated alterationalterations in intrinsic SAN cell behavior and associated changes in brainbrain-heart communication play cent ral role roles in the development of SAN cell pacemaker failure. This minimini-review provides integrated insights into the molecular mechanisms underlying the effects of aging on deterioration in beating rate and contractility of the heart in animal models and in apparently healthy humans.